Manhaj al-wasatiyah : ta'rifuhu wa mabda'uhu wa tatbiquhu - Abdullah Md. Zin (Putrajaya, Malaysia : Institut Wasatiyyah Malaysia, 2013)
On moderation in Islam and the implementation in Malaysia.
Includes bibliographical references (page 40-41)
Keywords: Moderation -- Religious aspects -- Islam; Liberalism -- Malaysia; Liberalism -- Religious aspects -- Islam